1989
DOI: 10.1002/app.1989.070380104
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking structure of keratin. II. Intermolecular and intramolecular crosslinks in potassium‐cyanide‐treated wool fibers

Abstract: SynopsisThe crosslinking structure of keratin fibers has been investigated. The reaction of wool with aqueous KCN was studied by means of chemical and physical methods. Quantitative conversion of disulfide (SS) groups of the cystine (Cys) residues into stable thioether (S) linkages was confirmed. In terms of mechanically effective and noneffective crosslinkages, the amounts of intermolecular and intramolecular crosslink in the KCN-treated wools were determined from the analysis of the corresponding amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Reduction and oxidation of disulfide bonds belong to the common methods for keratin isolation. Reduction of keratin involves use of 2‐mercaptoethanol (Balaji et al, ; Fujii & Li, ; Kakkar, Madhan, & Shanmugam, ; Reichl, ; Schrooyen, Dijkstra, Oberthür, Bantjes, & Feijen, ; Tanabe, Okitsu, & Yamauchi, ; Yamauchi, Yamauchi, Kusunoki, Kohda, & Konishi, ), dithiothreitol (DTT), dithioerythritol (Vasconcelos et al, ; Yang, Zhang, Yuan, & Cui, ), thioglycolic acid (Hill et al, ; Zabashta, Kasprova, Senchurov, & Grabovskii, ), glutathione (Schrooyen, Dijkstra, Oberthür, Bantjes, & Feijen, ), salts of hydrocyanic acid (Arai, Sakamoto, Naito, & Takahashi, ), bisulfites (Tonin et al, ), and m‐ bisulphites (Aluigi et al, ; Vasconcelos et al, ) to solubilize the protein. Many keratins can remain trapped within the protective structure, and usually a hydrogen‐bond breaking agent, such as urea, thiourea, transition metal hydroxides, surfactants, and combinations thereof, are included in the extractant to unfold or denature the protein (Torchinsky, ).…”
Section: Solubilization Of Keratinsmentioning
confidence: 99%
“…Reduction and oxidation of disulfide bonds belong to the common methods for keratin isolation. Reduction of keratin involves use of 2‐mercaptoethanol (Balaji et al, ; Fujii & Li, ; Kakkar, Madhan, & Shanmugam, ; Reichl, ; Schrooyen, Dijkstra, Oberthür, Bantjes, & Feijen, ; Tanabe, Okitsu, & Yamauchi, ; Yamauchi, Yamauchi, Kusunoki, Kohda, & Konishi, ), dithiothreitol (DTT), dithioerythritol (Vasconcelos et al, ; Yang, Zhang, Yuan, & Cui, ), thioglycolic acid (Hill et al, ; Zabashta, Kasprova, Senchurov, & Grabovskii, ), glutathione (Schrooyen, Dijkstra, Oberthür, Bantjes, & Feijen, ), salts of hydrocyanic acid (Arai, Sakamoto, Naito, & Takahashi, ), bisulfites (Tonin et al, ), and m‐ bisulphites (Aluigi et al, ; Vasconcelos et al, ) to solubilize the protein. Many keratins can remain trapped within the protective structure, and usually a hydrogen‐bond breaking agent, such as urea, thiourea, transition metal hydroxides, surfactants, and combinations thereof, are included in the extractant to unfold or denature the protein (Torchinsky, ).…”
Section: Solubilization Of Keratinsmentioning
confidence: 99%
“…In addition, they found that there were at least two types disulfide groups in keratin fibers by the studies of thermoelastic examination of keratin fibers: one group being readily reduced by thioglycolic acid in hydrophilic environment and the other being readily reduced by tri-n-butylphosphine in the regions of hydrophobic environment (5)(6)(7)(8). The aim of this study is to clarify the fine structure of hair fiber components, especially CMC of cuticle, by dimensional changes resulting from reduction and grafting at ultrastructual level .…”
Section: Introductionmentioning
confidence: 99%